EVALUATION OF SOME PRINCIPLES OF MEDICAL EDUCATION IN THE LIGHT OF THE QURAN: Principles of Medical Education in The Quran - Uddin, Rehan; Khan, Farrukh Hayat; Safdar, C. Aqeel (Pakistan Armed Forces Medical Journal, 2015)
Objective: The purpose of this study is to highlight the presently used medical educational principles highlighted in the Quran, analyze them and correlate them to derive lessons facilitating their implementation. Study Design: Mixed method study. Place and Duration of Study: Department of Medical Education, CMH Medical College, Lahore; January to December, 2013. Material and Methods: Verses of Quran from different Tafaseer (Explanation of Quran by renowned Muslim Scholars) related to education were identified. Help from dictionaries and encyclopedias available on internet were sought for true meanings and connotations. The ideas derived from the medical educational research were applied to find educational principles and compared to existing medical educational philosophies. Learner response system was used to gather educationalists opinions. Results: Principles of medical education which have been learned over last few decades and are now globally accepted and practiced were already there in Quran for last 1400 years. The common principles discovered and discussed were: Simplicity, Learning in steps, Paced learning, Identification of important, Critical thinking, Inductive reasoning, Use of examples, and Repetition. Most of these are core principles of medical education. Conclusion: Adult learning principles are already present in the Quran. In the propagation of these modern medical educational principles, references to Quran may help to understand their deeper perspectives. It may expedite the wider acceptance by educationalists in the Muslim countries.